A platform for analysis and control design: Emulation of energy storage flywheels on a rotor-AMB test rig. (February 2016) - Lyu, Xujun; Di, Long; Yoon, Se Young; Lin, Zongli; Hu, Yefa
Abstract: Energy storage flywheels supported on active magnetic bearings (AMBs) have attracted much attention both in the academia and in the industry due to their many advantageous features, such as short charging time, high specific energy, no pollution and long life span. Feedback control is essential in the operation of such AMB support systems. However, actual AMB suspended energy storage flywheels are not widely available for research on feedback control design. To provide an economic and effective platform for the study of AMB supported energy storage flywheels, including research on the design of their feedback controllers, we propose in this paper to emulate the operation of such flywheels on a rotor-AMB test rig we recently constructed. Specifically, the two AMBs located at the two ends of the rotor are used as supporting bearings, while the other two located at the rotor mid span and quarter span are used to emulate the generator negative stiffness and gyroscopic effects on the rotor dynamics caused by the flywheel disk. Simulation and experimental results are presented to show the effectiveness of the proposed emulation method.